Deconstructing and reconstructing fermented food microbiomes: revealing microbial interactions and developing new educational models - LANDIS, ELIZABETH. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2021.; Submitted to the Dept. of Biology.; Advisor: Benjamin Wolfe.; Committee: Julia Gouvea, Elizabeth Crone, and Erik Hom.; Keywords: Microbiology, Ecology, and Education.